Developing Evaluative Descriptive Text with Rebecca M. Valette’s Taxonomy and CLIL Approach - Khomsah, Arin Nur; Subyantoro, Subyantoro (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Learning evaluation  is an important factors of learning success. The results of monitoring and evaluating the implementation of the 2013 curriculum at the junior high school level in 2014 showed that one of the difficulties of educators in implementing the 2013 curriculum was assessment. The purpose of this study was to analyze the needs of teachers, produce characteristics, produce tools, find out the effectiveness of evaluation tools in composing description text with the taxonomy of Rebecca M. Valette and CLIL approach for grade VII junior high school students. The research method used in this study was the Research and Development research design (research and development) from Borg and Gall. The evaluation tools compiled description texts using Rebecca M. Valette's taxonomy and the CLIL approach were stated to be effective and feasible to assess aspects of the knowledge, attitudes, and skills of Indonesian language learning in seventh grade junior high schools, especially the basic competencies in composing description texts. This is because in this tool has been equipped with the aim of learning Indonesian language which includes aspects of language, culture, and communication in accordance with the 2013 curriculum. It was expected this evaluative instrument could  support  assessment of Indonesian language learning in 2013 curriculum  based on text.